Lateral carbon fluxes and CO2 outgassing from a tropical peat-draining river - A., Mujahid (Copernicus Publications on behalf of the European Geosciences Union., 2015)
Tropical peatlands play an important role in the global carbon cycle due to their immense carbon storage capacity. However, pristine peat swamp forests are vanishing due to deforestation and peatland degradation, especially in Southeast Asia. CO2 emissions associated with this land use change might not only come from the peat soil directly but also from peat-draining rivers. So far, though, this has been mere speculation, since there has been no data from undisturbed reference sites. We present the first combined assessment of lateral organic carbon fluxes and CO2 outgassing from an undisturbed tropical peat-draining river. Two sampling campaigns were undertaken on the Maludam River in Sarawak, Malaysia. The river catchment is covered by protected peat swamp forest, offering a unique opportunity to study a peat-draining river in its natural state, without any influence from tributaries with different characteristics. The two campaigns yielded consistent results. Dissolved organic carbon (DOC) concentrations ranged between 3222 and 6218 μmol L